2020
DOI: 10.1111/ijcp.13599
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, perception and practice of antibiotics usage among the pharmacy students

Abstract: An antibiotic is a type of antimicrobial substance active against bacteria, and widely used for the treatment and prevention of various bacterial infections. Antibiotics are the substance that are commonly produced by microorganism which act against other microorganisms. 1 According to the world health organization (WHO), more than 50% of medicines are incongruously prescribed, dispensed and utilised. Furthermore, around half of the patients take their medicines incorrectly. 2 The irrational use of medicine is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
6
2
Order By: Relevance
“…However, their study also showed that their level of knowledge increased as the years of education progressed [ 28 ]. Similar results were observed by Kandasamy et al, in which 54% of pharmacy students failed to recognize antibiotic resistance as a national problem [ 37 ]. In a separate study involving students studying pharmacy, veterinary science and biology, researchers found that most students were familiar with the term AMR and 79.4% were able to identify a poorly designed dosing regimen as a contributing factor towards AMR [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…However, their study also showed that their level of knowledge increased as the years of education progressed [ 28 ]. Similar results were observed by Kandasamy et al, in which 54% of pharmacy students failed to recognize antibiotic resistance as a national problem [ 37 ]. In a separate study involving students studying pharmacy, veterinary science and biology, researchers found that most students were familiar with the term AMR and 79.4% were able to identify a poorly designed dosing regimen as a contributing factor towards AMR [ 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, most of the respondents were not aware of the appropriate use of antibiotics which is in contrast to the results of Kandasamy et al. (2020). Also, self‐medication was found very common in this case because people use the prior prescription to buy antibiotics from pharma stores in case of the same symptoms like fever appeared again.…”
Section: Resultscontrasting
confidence: 97%
“…Moreover, they also stated that inappropriate antibiotic use was unethical and could cause harm to patients; consequently, appreciable knowledge of antibiotics is essential for student HCPs post-qualification. These findings were in contrast to recent studies from Saudi Arabia, where more than half of the studied pharmacy students were unaware that AMR is a health threat, and in Rwanda, where 37.6% of HCP students did not believe that antibiotics were being overused [80,94]. However, 83% of students in Rwanda were unfamiliar with the concept of antimicrobial stewardship and 49% had not discussed AMR as part of their education [80].…”
Section: Discussioncontrasting
confidence: 73%